Kinetics of xylose in hydrolysate using dilute sulphuric acid as catalyst. (6th August 2009) - Qi, Wei; Zhang, Suping; Xu, Qingli; Zhu, Zhenxing; , Zhengwei Ren, Yongjie Yan
In the technology of manufacturing fuel alcohol from biomass as feedstock, hydrolysis using dilute acid as catalyst is one way to produce fermentable saccharide. In this process, the yield of xylose is always low because of the degrading during the acid environment. In this paper, the degrading kinetics of xylose in the hydrolysate was investigated under the conventional process conditions of the hydrogen ion range from 0.05 to 0.2 mol L−1 and the temperature range from 150 to 200°C. Through the numerical calculation method, the kinetic parameters were estimated and the activation energy of xylose in the degrading reaction was obtained. The kinetic equations that correlated the effect of hydrogen ion concentration on the rate constants of the degrading reaction were established. Comparisons between calculated results and the experimental results have proved that the established kinetic model can satisfactorily predict the degradation behaviours of xylose in the acidic hydrolysate.